STUDI POTENSI SUMBERDAYA ALAM DI KAWASAN PESISIR KABUPATEN MINAHASA SELATAN - Durand, Swenekhe Sandra (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2010)
Fisheries and marine sectors have to be the main program of North Sulawesi economic development. Since the fisheries potency is large enough and the development is good in fishing, aquaculture and fish processing, the regional government has established the fisheries sub-sector as one of the development supporting factors. The study was carried out from February to July 2008 in South Minahasa Regency. Data collection was done through structured and unstructured interviews, field observations and documentations. The study used a qualitative descriptive analytical method in spite of quantitative data collections. South Minahasa is one of the regencies in North Sulawesi with the capital of Amurang, possesses an area of 1,591.65 Km2 (population of 201,293), consists of 17 districts, 154 villages, 815 small government units. Seven districts are in the coastal areas (Tenga,Sinonsayang,East Amurang, Amurang, West Amurang, Tumpaan and Tatapaan). The coastal natural recources of this regency are mangrove ecosystem, coral reef, and sea grasses. These ecosystems have an ecological integration that will affect future fisheries recources productivity. Fisherman of South Minahasa Regency are distributed in 17 districts. The potency of coastal fisheries recources and its development in SouthÂ  Minahasa Regency possesses 933 Ha of mangrove ecosystems, 1,349.6 Ha of coral reefs, and 1300 Ha of seagrass beds at Rap-Rap Wawontulap. Fishery society in Regency of Minahasa South arch gone the round in 17 districts. Sum up the fishery domestic a lot of there are in districts Amurang with the amount 563 RTP. In general fishery Society in Regency of Minahasa South arch conduct four fishery activity that is aquaculture, arrest, merchant and fish processor. Full scale aquaculture is 1.435 soul, sum up this gone the round in seven districts compassion, 236 soul in New districts Tompaso. To the effort fish arrest in the sea, do not all districts own the activity of fish arrest there's only seven districts (Tataapan, Tumpaan, Amurang East, Amurang, Amurang West, Tenga And Sinonsayang) full scalely is Fisherman catching fish in the sea 6.446 soul and which is a lot of there are in districts Tumpaan. For the fisherman of catching fish in public territorial water is only gone the round in five districts (Motoling West, Ranoyapo, New Tompaso, Maesaan And Modoinding), full scalely 59 soul and which is a lot of there are in fewest districts Modoinding there are in districts of Motoling West.